2021
DOI: 10.1007/s10557-021-07278-9
|View full text |Cite|
|
Sign up to set email alerts
|

The Comparative Effectiveness and Safety of Different Anticoagulation Strategies for Treatment of Left Atrial Appendage Thrombus in the Setting of Chronic Anticoagulation for Atrial Fibrillation or Flutter

Abstract: Purpose To compare effectiveness of different treatments for atrial fibrillation (AF) patients who were scheduled for cardioversion (CV) or ablation (CA) presenting with left atrium appendage (LAA) thrombus despite chronic oral anticoagulation therapy (OAC). Methods This was a retrospective cohort study. We analyzed 2014–2019 medical records of patients scheduled for CV or CA of AF who were diagnosed with LAA thrombus despite optimal OAC and had a follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…[21] Another retrospective cohort study showed that LAAT resolution in patients already undergoing OAC therapy may require a change of previous oral anticoagulant but the overall effectiveness of dissolution was approximately 50%. [46] In patients with AF who received LAAEI during left atrial linear lesions or cryoballoon ablation, the thrombus resolved in 72.2% of patients after adjusting the anticoagulant treatment regimen, but there were still 23.5% of AF patients for whom LAAT persisted. LAAC was a reliable alternative in situations when the anticoagulants regimen was ineffective.…”
Section: 6%mentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Another retrospective cohort study showed that LAAT resolution in patients already undergoing OAC therapy may require a change of previous oral anticoagulant but the overall effectiveness of dissolution was approximately 50%. [46] In patients with AF who received LAAEI during left atrial linear lesions or cryoballoon ablation, the thrombus resolved in 72.2% of patients after adjusting the anticoagulant treatment regimen, but there were still 23.5% of AF patients for whom LAAT persisted. LAAC was a reliable alternative in situations when the anticoagulants regimen was ineffective.…”
Section: 6%mentioning
confidence: 99%
“…[44,45] After 3-6 months of anticoagulation for LAAT, the left atrial CTA and TEE evaluation showed LAAT resolution, partial resolution, or an unchanged thrombus, and long-term anticoagulant therapy was necessary. [46] Thromboembolic events arising from thrombus shedding during the process of thrombus remission cannot be predicted or prevented. In addition, the biggest problem of continuous long-term anticoagulant therapy for elderly patients with AF is intolerance, especially to VKA, which require regular monitoring of the international normalized ratio (INR).…”
Section: 6%mentioning
confidence: 99%
“…Kolakowski et al specifically reported on chronically anticoagulated patients for AF or atrial flutter and still had LAA thrombus detected by the TOE. 46 They showed that nearly 52% of patients had LAA thrombus dissolution regardless of the number of treatment cycles employed. In contrast, any change in treatment (switch to a different OAC) was associated with increased odds of success.…”
Section: Oral Anticoagulant Strategies In Persistent Left Atrial Appe...mentioning
confidence: 99%
“…switch to an anticoagulant with a different mechanism, switch to an anticoagulant with a similar mechanism of action, switch to another anticoagulant with an added antiplatelet agent, adding a second anticoagulant drug or deliberate no change in treatment). 46 However, combining an OAC and antiplatelet failed to show a statistical advantage in efficacy over any other antithrombotic regimen. It can be concluded that the role of antiplatelet addition for this indication is highly limited and currently not supported by the evidence except in cases in which a patient has another indication, such as concomitant coronary artery disease.…”
Section: Adding Antiplatelet To Anticoagulation Drugs For the Pharmac...mentioning
confidence: 99%
“…The management of these patients can be challenging, and consists of various therapeutic regiments, including a higher international normalized ratio (INR) target (3–3,5) in those under VKA or a switch to distinct anticoagulation therapy – VKA, NOACs, low-molecular-weight heparin (LMWH), or unfractionated heparin (UFH) [ 2 , 7 , 10 ]. Even so, the overall effectiveness of a second anticoagulation approach for thrombus dissolution is only 42.6% [ 11 ]. The are limited therapeutic options for patients with LAA thrombus unresponsive to various anticoagulation regimens [ 12 ].…”
Section: Introductionmentioning
confidence: 99%